2005
DOI: 10.1111/j.1440-1681.2005.04218.x
|View full text |Cite
|
Sign up to set email alerts
|

CARDIOVASCULAR AUTONOMIC REGULATION IN SUBJECTS WITH NORMAL BLOOD PRESSURE, HIGH–NORMAL BLOOD PRESSURE and RECENT‐ONSET HYPERTENSION

Abstract: 1. In the present study, we tested the hypothesis that heart rate variability (HRV) is reduced in recent-onset hypertension and that pressor responses to standard autonomic reflex tests are not any different in hypertensives compared with normotensives. We also hypothesized that subjects with high-normal blood pressure (BP) would be distinguishable from normotensives on the basis of short-term HRV indices. 2. Three groups of subjects, each consisting of 15 men and 10 women, were examined. The first group consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 36 publications
4
24
2
2
Order By: Relevance
“…This is consistent with our previous study in stage I hypertensive adults indicating exaggerated neurocirculatory responses to graded intensities of isolated metaboreflex activation (11). Previous studies have reported that the pressor response to exercise in adults with high-normal systolic BP is not different than the response in NTN adults (21,50). This is somewhat contradictory to the findings of the present investigation; however, such differences are likely a result of differing inclusion criteria and BP classifications.…”
Section: Discussioncontrasting
confidence: 57%
“…This is consistent with our previous study in stage I hypertensive adults indicating exaggerated neurocirculatory responses to graded intensities of isolated metaboreflex activation (11). Previous studies have reported that the pressor response to exercise in adults with high-normal systolic BP is not different than the response in NTN adults (21,50). This is somewhat contradictory to the findings of the present investigation; however, such differences are likely a result of differing inclusion criteria and BP classifications.…”
Section: Discussioncontrasting
confidence: 57%
“…The higher the blood pressure, the greater the chance of heart attacks, heart failure, stroke, and kidney disease in subjects with a blood pressure ranging from 115/75 to 185/115 mm Hg (19). There has been a hospital-based study of CAF in subjects with high-normal blood pressure of 130 to 139/85 to 89 mm Hg (20), rather than the revised value of 120 to 139/80 to 89 mm Hg. The findings of CAF alteration in normotensive subjects with a family history of hypertension (FHH) have been inconsistent (21)(22)(23), and these studies define normotension as a blood pressure Ͻ140/90 mm Hg (21)(22)(23), not the revised value of Ͻ120/80 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…7 A alteração da homeostase cardiovascular em pacientes hipertensos mostrou causar um desequilíbrio simpatovagal caracterizado pela diminuição da modulação vagal e pelo aumento da atividade simpática. 8 A resposta à laringoscopia é significativamente diferente em pacientes hipertensos, em comparação com pacientes normotensos. As alterações da pressão arterial que se desenvolvem imediatamente após a indução da anestesia são muito maiores em pacientes hipertensos.…”
Section: Introductionunclassified